The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/bmjgh-2017-000313
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cost-effectiveness, comparing traction to intramedullary nailing of femoral shaft fractures, in the less economically developed context

Abstract: IntroductionFemoral shaft fractures carry considerable morbidity and are increasingly common in less economically developed countries (LEDCs). Treatment options include traction and intramedullary (IM) nailing but in a limited-resource environment; cost-effectiveness is fundamental to policy development.The objective herein was to evaluate the cost-effectiveness of moving from traction to IM nailing for femoral shaft fractures, in adults, in LEDCs. Incorporating a systematic review of complications and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
9
0
1
Order By: Relevance
“…However, nonoperative treatment using skeletal traction (ST) for at least 6 weeks remains the mainstay treatment for these fractures in low-resource settings (Hollis et al 2015, Kramer et al 2016. Nonoperative treatment is associated with increased risk of both medical and surgical complications, reported as high as 55% in some studies (Bucholz and Jones 1991, Doorgakant and Mkandawire 2012, Kramer et al 2016, Parkes et al 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, nonoperative treatment using skeletal traction (ST) for at least 6 weeks remains the mainstay treatment for these fractures in low-resource settings (Hollis et al 2015, Kramer et al 2016. Nonoperative treatment is associated with increased risk of both medical and surgical complications, reported as high as 55% in some studies (Bucholz and Jones 1991, Doorgakant and Mkandawire 2012, Kramer et al 2016, Parkes et al 2017.…”
mentioning
confidence: 99%
“…In Malawi, femoral shaft fractures are most commonly treated by ST. IMN, when performed, is done using the SIGN IM nail, which is donated by SIGN Fracture Care International (Richland, WA, USA) (Shah et al 2004). Most studies comparing IMN with ST in LICs used conventional measures such as fracture union, complications, and range of motion (Swai 2005, Kamau et al 2014, Parkes et al 2017. No prior study has measured quality of life or function using a validated patient-reported outcome instrument to compare ST and IMN in any context.…”
mentioning
confidence: 99%
“…At present, the authors point to an increase in treatment costs. This is due to increasing perioperative costs and high costs of the implants [20]. Consequently, the growing group of supporters includes more and more traumatologists using stainless steel intramedullary nails.…”
Section: Discussionmentioning
confidence: 99%
“…Sadly, in LMICs only a small percentage of patients have access to locked IM nailing [9,10]. Less than optimal methods of treatment like prolonged traction and treatment by traditionalists is still common-place [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%